Noise Making: The Rise of the Noisician in Malaysia - Mokhtar, Muhamad Hafifi bin (Malaysian Journal of Music, 2015)
This paper considers the existence, culture and politics of an emergent Malaysian ‘Noise Scene’ through an exploration of the history of Noise in the twentieth century both in Malaysia and beyond, the views of several local practitioners, the author’s own experience of the noise scene, and a survey of Noise supporters to expand our understanding in ways that reflect the Malaysian Noise Scene. Prepared by a practicing ‘Noisician’, an autoethnographic or 'insider-outsider' stance is used in searching for answers to the research questions. The focus of this paper is on the perspectives, practice, politics and relationship to Malaysian culture of the local performers and their supporters. In preparing this research, the author made several assumptions about the current Noise Scene, but found that these were challenged by the results, with the outcomes shedding new knowledge for the author himself.